KEBIJAKAN PENGADAAN GURU MASA ORDE BARU : PENGARUHNYA TERHADAP SISTEM PENDIDIKAN DAN KEGURUAN DI INDONESIA - Adrian Farsyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The New Order was an era of development and progress in Indonesia led by President Soeharto. The high need for teaching staff to achieve the goal of equitable education became a serious problem in the midst of the high illiteracy rate of Indonesian society at that time. Teacher procurement is a crucial solution to create and map competent and qualified teaching staff in Indonesia. This study aims to identify and analyse the teacher procurement system during the New Order era and its influence on the current education and teaching system in Indonesia. The data obtained is secondary data derived from various written sources which are then reviewed by using literature study techniques and analysed qualitatively. The results showed that the procurement of teachers during the New Order era had a significant influence on the education system and implementation in Indonesia from time to time, especially on the current teacher education system in Indonesia, which is commonly known as the Teacher Professional Education (PPG) programme. This has a positive impact on the Indonesian education system in order to provide a much higher quality education for Indonesia's younger generation.